KEEFEKTIFAN MODUL AJAR INVERS MATRIKS BERBASIS PROJECT-BASED LEARNING TERKAIT KEMAMPUAN KONEKSI MATEMATIS MAHASISWA - Fadlurrochman, Rizqon Fuadi; Ihsan, Muhammad (Uninus Journal of Mathematics Education and Science (UJMES), 2024)
This research is motivated by the lack of teaching materials that meet the needs of curriculum development and the limited mathematical connection abilities of students in the topic of matrix inversion, as well as the ineffectiveness of available teaching materials. The aim of this research is to determine the effectiveness of a teaching module developed using the Project-Based Learning model. The research method used in this study is the Design Research method with the Plomp model. The instruments used are mathematical connection ability tests, affective domain questionnaires, affective domain observations, and psychomotor domain observations. Data were analyzed using percentages interpreted according to their qualifications. Based on the analysis, it can be concluded that the teaching module developed is effective for use in the learning process. It is recommended that the teaching module be used in both school and university learning.